2019
DOI: 10.7759/cureus.5440
|View full text |Cite
|
Sign up to set email alerts
|

Infections in Deep Brain Stimulator Surgery

Abstract: Introduction: Deep brain stimulation has emerged as an effective treatment for movement disorders such as Parkinson’s disease, dystonia, and essential tremor with estimates of >100,000 deep brain stimulators (DBSs) implanted worldwide since 1980s. Infections rates vary widely in the literature with rates as high as 25%. Traditional management of infection after deep brain stimulation is systemic antibiotic therapy with wound incision and debridement (I&D) and removal of implanted DBS hardware. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 12 publications
1
24
0
1
Order By: Relevance
“…A further, more recent meta‐analysis examining the rate of wound complications necessitating hardware removal determined a rate of 3.8% per patient (18), though this may underestimate the true infection rate given that a significant proportion of infections may be managed without explantation (e.g., see case 3) (19). Examination of even more recent case series published within the last three years yields similar figures of between 0% and 10.9% with the proviso of significant heterogeneity in the way infection was defined (e.g., the inclusion of skin erosion without signs of infection), denominators used (e.g., patients, procedures, or implants), duration of follow‐up, inclusion of revision surgery in addition to primary implants, surgical technique, anti‐infection measures trialed during the studies, and patient factors (14,18,20–42).…”
Section: Discussionmentioning
confidence: 87%
“…A further, more recent meta‐analysis examining the rate of wound complications necessitating hardware removal determined a rate of 3.8% per patient (18), though this may underestimate the true infection rate given that a significant proportion of infections may be managed without explantation (e.g., see case 3) (19). Examination of even more recent case series published within the last three years yields similar figures of between 0% and 10.9% with the proviso of significant heterogeneity in the way infection was defined (e.g., the inclusion of skin erosion without signs of infection), denominators used (e.g., patients, procedures, or implants), duration of follow‐up, inclusion of revision surgery in addition to primary implants, surgical technique, anti‐infection measures trialed during the studies, and patient factors (14,18,20–42).…”
Section: Discussionmentioning
confidence: 87%
“…However, in cases of obvious infection, this will very likely fail. Furthermore, there is a risk of intracranial infection if the bacteria migrate from the IPG to the electrodes [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Other authors have not shown that the use of VP is beneficial. [ 6 ] In our practice, we recommend the use of intrawound VP since it increases the antibiotic concentrations locally[ 3 ] without further risks, thus decreasing the incidence of infection.…”
Section: Discussionmentioning
confidence: 99%